A Tale of Two Toxins: Helicobacter Pylori CagA and VacA Modulate Host Pathways that Impact Disease - Jones, Kathleen R.; Whitmire, Jeannette M.; Merrell, D. Scott (Frontiers in Microbiology, 2010)
Helicobacter pylori is a pathogenic bacterium that colonizes more than 50% of the world’s population, which leads to a tremendous medical burden. H. pylori infection is associated with such varied diseases as gastritis, peptic ulcers, and two forms of gastric cancer: gastric adenocarcinoma and mucosa-associated lymphoid tissue (MALT) lymphoma. This association represents a novel paradigm for cancer development; H. pylori is currently the only bacterium to be recognized as a carcinogen. Therefore, a significant amount of research has been conducted to identify the bacterial factors and the deregulated host cell pathways that are responsible for the progression to more severe disease states. Two of the virulence factors that have been implicated in this process are CagA and VacA, which are cytotoxins that are injected and secreted by H. pylori, respectively. Both of these virulence factors are polymorphic and affect a multitude of host cellular pathways. These combined facts could easily contribute to differences in disease severity across the population as various CagA and VacA alleles differentially target some pathways. Herein we highlight the diverse types of cellular pathways and processes targeted by these important toxins.